The nation in turmoil : civil rights and the Vietnam War, 1960-1973 - Brown, Gene. frey50 (New York : Twenty-First Century Books, 1993)
Presents primary source materials covering such major social and political events in United States history as the civil rights movement, the Great Society, and the Vietnam war and anti-war sentiment.
Includes bibliographical references and index.
Keywords: Vietnamese Conflict, 1961-1975 -- Sources -- Juvenile literature; Civil rights movements -- History -- Sources -- Juvenile literature. -- 20th century -- United States; United States -- History -- Sources -- Juvenile literature. -- 1961-1969; United States -- History -- Sources -- Juvenile literature. -- 1969-; United States -- History -- Sources. -- 1969-; United States -- Social conditions -- Sources. -- 1960-1980